An investigation on cognitive and behavioural effects of donepezil on autistic children in Winter 2020 in Gorgan Taleghani pediatric hospital - Ghahreman, Yamin; Hosseini, Seyed Ahmad; Hassani, Saeed; Derakhshanpour, Firouzeh; Hassani, Mohammad Javad; Hosseini, Parnian (Iranian Journal of Child Neurology, 2023)
Objectives The present investigation has been done to study the behavioral effects of donepezil in autistic children, given that not much research has been carried out concerning using this drug for treating autism. Materials & Methods A cross-sectional and analytic-descriptive study was done on twentypatients with autism, aged 4-17, who visited the neurology clinic of Gorgan’s Taleghani Pediatric Hospital and Yasha Pediatric Autism Clinic, Iran from 2019 to 2020. Demographic information, including sex, age, father’s education, mother’s education ,patient’s education, family status, other problems, and ethnicity, were documented using a checklist, having been filled in during interviews with the parents. Before the trial, ABC cognitive and behavioral tests were taken to determine the children’s current status. After the tests, these children received a daily dose of donepezil (10mg) before sleep for three months. At the end of the three months, the cognitive and behavioral tests were taken from the children once again. In order to analyze the effects of different factors on the studied variables, including irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech before and after the administration of donepezil in patients, a generalized linear model and to test the effects of donepezil on the studied variables, paired t-test was used. Results In this study, twenty patients were registered for the investigation, 12 (60%) male and eight (40%) female. Age groups 5-6 had the highest frequency, and age group 17 had the lowest. Regardingthe parents’ education, the highest frequency was for bachelor’s degrees, and the lowest was for less-than-high school education and master’s degree. The highest frequency for the patients’ education was kindergarten (60%), and then groups without education (20%) and elementary school-level education (15%). Most of the studied patients (80%) did not have other problems besides autism, and only 20% had other problems besides autism. The family status of 15% of the families was ‘separated,’ and ethnically, most patients (80%) were Fars, while the rest (20%) were Turkmen. None of the analyzed factors (age, sex, father’s education, mother’s education, patient’s education, other problems, family status, and ethnicity) had a significant effect on the studied variables after the administration of donepezil. Among the studied variables prior to the administration of donepezil and among the analyzed factors, the father’s education, the patient’s education, other problems, and family status had only a significant effect on stereotypic behavior. The present research findings of the present research indicated that all the studied variables, including irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech, were significantly decreased toward the desired goal. The decreased amounts in irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech after the administration of donepezil were, respectively, 38%, 44%, 54%, 41%, and 54% and on average, these behaviors were reduced by 46%. Conclusion The present investigation has shown that all the studied variables, including irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech, were significantly decreased towards the desired goal by 46%. This significant decrease is indicative of the effectiveness of the treatment of autism patients with donepezil, and therefore, this drug can be placed as a prominent and essential part of the medical therapy of autism.